A fresh start? Understanding the impact of parents’ forced migration on young children’s development in a country of resettlement - Robinson, J (My University, 2012)
For a range of practical reasons, most studies of the development and wellbeing of the children of forcibly displaced parents have a number of limitations. They usually focus on a limited age range: most research focuses on middle childhood and adolescence. They usually rely on samples of convenience and these samples are usually drawn from a single geographic location: most research focuses on a single camp in a country of first asylum or a single urban centre in a country of resettlement. Few studies collect longitudinal data, and few provide insight into the unique features of forced migration as a context for development by comparing patterns of development for the children of forced and voluntary migrants. The current study seeks to overcome some of these limitations by exploiting the inclusion of children of forced and voluntary migrants in a large archival database in one of the main countries for resettlement of forcibly displaced people. The Longitudinal Study of Australian Children (LSAC) focuses on the development of infants and young children. It involves two cohorts: children who were infants (0-1 years of age) in 2003-2004, and children who were of preschool age (4-5 years of age) in 2003-2004. The study involves representative samples of children now living in urban and rural areas of all states and territories in Australia. Longitudinal data is collected data from both cohorts every two years. This paper focuses on data from both cohorts when the children were aged 4-6 years. It compares the developmental context, preschool/school adjustment, school readiness and emotional and behavioural problems of young children whose parents were born in: Non-English speaking countries that almost exclusively contribute forced migrants to Australia (e.g., Sudan, Afghanistan); Non-English speaking countries that almost exclusively contribute voluntary migrants to Australia (e.g., India, China); and Australia. Information about children’s developmental context and their social and emotional problems (Strengths and Difficulties Questionnaire) were obtained from parents and preschool/school teachers. Teachers also reported on preschool/school adjustment (Student-teacher Relationship Scale) and skills and competencies relevant for success at school. Children of forced migrants were more likely than children in other groups to experience disadvantage on several dimensions of their developmental context. Outcome variables differed in the extent to which parents’ migration status explained independent variance in outcomes after this has been accounted for. Both teacher- and parent-reports indicated a number of dimensions on which these children showed resilient development.
Keywords: Culture -- Immigrants; Education and Training -- School readiness; Disadvantage; Children -- Outcomes; Child Development; Childhood and child development; Learning, education and training; Migration and settlement; Disadvantage; Education and Training; Child Development; Culture; Children; Immigrants; Outcomes; School readiness; Childhood and child development; Learning, education and training; Migration and settlement